World's First Experience Treating TASC II C and D Tibial Occlusive Disease Using the Selution SLR Sirolimus-Eluting Balloon: Six-Month Results From the PRESTIGE Study. (August 2021) - Tang, Tjun Yip; Yap, Charyl; Soon, Shereen Xue Yun; Chan, Sze Ling; Lee, QingWei Shaun; Yap, Hao Yun; Tay, Hsien Ts'ung Luke; Chong, Tze Tec
Purpose: The performance of sirolimus-coated devices has not been studied in patients with chronic limb-threatening ischemia patients. PRESTIGE aims to investigate the 6-month efficacy and safety profile of the Selution Sustained Limus Release (SLR) sirolimus-eluting balloon for treatment of TASC II C and D tibial occlusive lesions in patients with CLTI. Materials and Methods: PRESTIGE is a pilot prospective, nonrandomized, single-arm, multi-investigator, single-center clinical study. Endpoints were adverse event-free survival at 1 month, technical success rate, primary tibial patency at 6 months, limb salvage success, target lesion revascularization (TLR), and amputation free survival (AFS). Results: A total of 25 patients were included. There were 17 (68.0%) males; mean age, 63.7±9.73 years. CLTI severity was based on the Rutherford scale (R5=25/25; 100.0%). Significant comorbidities included diabetes mellitus (n=22; 88.0%) and end-stage renal failure (n=11; 44.0%). A total of 33 atherosclerotic lesions were treated (TASC II D=15 (45.5%)). Mean lesion length treated was 191±111 mm. Technical success was 100%. Primary tibial patency at 6 months was 22/27 (81.5%) and freedom from clinically driven TLR was 25/30 (83.3%). AFS was 21/25 (84.0%; 3 deaths and 1 major lower extremity amputation). Mean Rutherford score improved from 5.00 at baseline to 1.14±2.10 (p<0.05) at 6 months. There was a wound healing rate of 13/22 (59.1%) and 17/21 (81.0%) at 3 and 6 months respectively. Conclusions: Selution SLR drug-eluting balloon is a safe and efficacious modality in treating complex tibial arterial occlusive lesions in what is an otherwise frail cohort of CLTI patients, with a high prevalence of diabetes and end-stage renal failure. Technical and clinical success rates are high and 6-month target lesion patency and AFS are more than satisfactory.